Letter from Edward N. Kent to James Curtis Booth, November 28, 1860 - Kent, Edward (1860)
Edward N. Kent of the United States Assay Office at New York discusses brittle gold and cupel.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; United States. Assay Office, New York City